2022
DOI: 10.1002/humu.24445
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the phenotypic variability of MORC2 gene mutations: From Charcot‐Marie‐Tooth disease to late‐onset pure motor neuropathy

Abstract: MORC2 gene encodes a ubiquitously expressed nuclear protein involved in chromatin remodeling, DNA repair, and transcriptional regulation. Heterozygous mutations in MORC2 gene have been associated with a spectrum of disorders affecting the peripheral nervous system such as Charcot-Marie-Tooth (CMT2Z),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A previously reported patient with an adult-onset PD-SMA carried a variant in the MORC2 gene. 18 One patient with an infantile-onset PD-SMA carried a homozygous pathogenic variant in the DNAJB2 gene (AR). The specific genetic variants can be seen in eTable 1 ( links.lww.com/NXG/A614 ).…”
Section: Resultsmentioning
confidence: 99%
“…A previously reported patient with an adult-onset PD-SMA carried a variant in the MORC2 gene. 18 One patient with an infantile-onset PD-SMA carried a homozygous pathogenic variant in the DNAJB2 gene (AR). The specific genetic variants can be seen in eTable 1 ( links.lww.com/NXG/A614 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, progress in genome-wide association studies has identified several independent genetic loci of MORC2 for diseases. For instance, MORC2 mutations are associated with some disorders, 34 , 35 , 36 including Charcot-Marie-Tooth (CMT) disease, 37 , 38 , 39 , 40 , 41 spinal muscular atrophy, 24 , 42 , 43 and neurological disorders, 44 especially Charcot-Marie-Tooth disease type 2Z (CMT2Z), 38 , 45 thus allowing a better understanding of the genetic architecture of MORC2. Mounting evidence has shown that mutations in MORC2 may be strongly associated with the development of multiple cancers.…”
Section: Mutationmentioning
confidence: 99%
“…It was found to be highly expressed in human embryonic and adult neural tissues and dynamically regulated in the developing and mature murine nervous systems [ 13 ]. Functional assays have found that MORC2 variants affect neurone survival, apoptosis, neurite outgrowth, and abnormal axon morphology in keeping with the axonal neuropathy seen in patients with MORC2 -related disorders [ 13 , 14 ]. Furthermore, MORC2 may have a role in tumorigenesis, promoting the proliferation, invasion, and migration of glioma by inactivation of PTEN/PI3K/AKT signaling [ 15 ].…”
Section: Introductionmentioning
confidence: 99%